Gender-related differences in changes of estimated bleeding risk in patients on dual antiplatelet therapy: the RE-SCORE multicenter prospective registry. (17th November 2022) - Pelliccia, Francesco; Gragnano, Felice; Pasceri, Vincenzo; Marazzi, Giuseppe; Cacciotti, Luca; Placanica, Attilio; Niccoli, Giampaolo; Palmerini, Tullio; Speciale, Giulio; Granatelli, Antonino; Calabrò, Paolo
Abstract: The risk of bleeding as predicted by the PRECISE-DAPT score can vary over time after percutaneous coronary intervention (PCI). We sought to compare the predictive ability of the PRECISE-DAPT score calculated at baseline and reassessed during follow-up in male and female patients undergoing PCI. The RE-SCORE was a multicenter, prospective registry including patients undergoing PCI treated with dual antiplatelet therapy (DAPT) for 1 year. The primary endpoint was Bleeding Academic Research Consortium (BARC) type 2, 3 or 5 bleeding. The PRECISE-DAPT score was determined for each patient at the time of PCI and at 1, 4 and 8-month follow-up visits or before the occurrence of an endpoint event. A total of 480 patients undergoing PCI were included. At baseline, median PRECISE-DAPT score was similar in males (23.2 [IQR 20.1–24.2]) and females (23.4 [IQR 20.2–25.3]; p = .22). During follow-up, an increase in the PRECISE-DAPT occurred significantly more often in females (44%) than in males (23%; p < .001). The discrimination of the PRECISE-DAPT score calculated at baseline was marginal in both males (c-index = 0.59, 95% CI: 0.51–0.65) and females (c-index = 0.55, 95% CI: 0.49–0.60). The discriminative ability of the score reassessed at follow-up was excellent in females (c-index = 0.84; 95% CI: 0.77–0.91) but remained modest in males (c-index = 0.61; 95% CI: 0.55–0.70). The bleeding predictive ability of the PRECISE-DAPT score can vary over time, more commonly in females than males. The discrimination of the score calculated during follow-up appeared improved in females but remained modest in males. Clinical Trial Registration - ClinicalTrials.gov Identifier: NCT03526614